Antigua and Barbuda. Significant achievements 2012 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2015)
The main activities carried out by the Institute in Antigua and Barbuda during 2012 are identified, with respect to the needs and interests of the country, strengthening issues such as food security, technologies, marketing, agricultural development and the use of biodigesters. Finally, the inclusion of young people in agriculture, in waste management and in the value chains of pigs and small ruminants was supported.